Queen cells acceptance rate and royal jelly production in worker honey bees of two Apis mellifera races. - Khalid Ali Khan; Hamed A Ghramh; Zubair Ahmad; Mogbel A A El-Niweiri; Mohamed Elimam Ahamed Mohammed (PLoS ONE)
Royal jelly (RJ) is an acidic yellowish-white secretion of worker honey bee glands, used as food material of worker bee larvae for the first three days and queen bee larvae for the entire life. It is commercially used in cosmetics and medicinal industry in various parts of the world. This study determined the queen cell acceptance rate and RJ production difference among Italian and Carniolan bee races. Furthermore, the effect of plastic cup cell priming media, diets and seasons were tested on the larval cell acceptance rate and RJ yield of both races. The results indicated that average queen cell acceptance rate was significantly (p<0.001) higher in Italian race (75.53 ± 1.41%) than Carniolan race (58.20 ± 1.30%). Similarly, mean RJ yield per colony significantly (p<0.001) differed between both bee races, which were 13.10 ± 0.42 g and 9.66 ± 0.43 g, in Italian and Carniolan races, respectively. Moreover, priming media, diets and seasons significantly (p<0.001) affected queen cell acceptance rate and RJ production of both bee races. This study would help breeders to select the bees with higher-level of queen cell acceptance rate and RJ production in the future.